Analysis of The Key Success Factors of Electronic Procurement (E-Proc) Projects at Ministry X - Rully Priyatna; Ali Sunandar (LPPM NAROTAMA UNIVERSITY, Indonesia, 2021)
E-Proc or Electronic Procurement, namely procurement of goods and services electronically, according to Presidential Regulation Number 16 Year 2018, the Procurement of Goods / Services is conducted electronically using an information system consisting of an Electronic Procurement System and a support system. The purpose of this study is to study the dominant factors. In this study sixteen variables were used which were divided into 2 categories, namely the human factor category and the technology characteristic factor category, each consisting of variables. The questionnaire method was chosen as a source of data distributed to service users and service providers, the results of the questionnaire obtained will be tested for Validity and Reliability Test using statistical applications and Relative Importance Index (RII) Analysis. The five most dominant factors will be selected as research results, and it is expected that research factors can be studied for other Ministries / Institutions in implementing the E-Proc system.